(untitled) (GnosisWisdom, 2025)
Water is a vital resource for both human health and social and economic development; however, its quality can be compromised by adverse environmental conditions and human intervention. Significant challenges still persist regarding access to safe drinking water, especially in rural areas where treatment and monitoring systems are often limited. Within this context, the present study aimed to evaluate the physicochemical characteristics of water intended for human consumption in the population centers of San Carlos, Viñas, and the district of Pampas, located in the province of Tayacaja, Huancavelica. A descriptive and quantitative methodological approach was applied, using a stratified sampling design that covered various points in the distribution system, including catchment sources, reservoirs, and supply networks. Physicochemical indicators such as pH, turbidity, electrical conductivity, temperature, and residual chlorine were examined, and the results were compared against the limits established by national regulations. The findings revealed temporal variations in water composition, with particular emphasis on fluctuations in turbidity and residual chlorine levels. Although the recorded values generally remained within acceptable ranges, latent public health risks were identified, linked to inconsistent disinfection and the presence of suspended solids.